1997
DOI: 10.1148/radiology.205.3.9393545
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic echo-planar imaging of the breast: experience in diagnosing breast carcinoma and correlation with tumor angiogenesis.

Abstract: The T1 value remains important in more precise quantitative estimation of gadopentetate dimeglumine uptake in breast tumors, which helps improve the specificity of dynamic imaging. Tumor MVD affects the contrast medium enhancement of breast lesions, but other factors contribute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(90 citation statements)
references
References 0 publications
2
87
0
1
Order By: Relevance
“…Previously, the presence of increased blood flow in breast tumors has also been demonstrated using positron emission tomography (13), temporally-resolved contrast-enhanced MRI (14)(15)(16)(17), and color Doppler ultrasonography (18). Furthermore, an ipsilateral association between cancer and increased breast vascularity has been demonstrated using conventional MRI (19,20).…”
Section: Discussionmentioning
confidence: 98%
“…Previously, the presence of increased blood flow in breast tumors has also been demonstrated using positron emission tomography (13), temporally-resolved contrast-enhanced MRI (14)(15)(16)(17), and color Doppler ultrasonography (18). Furthermore, an ipsilateral association between cancer and increased breast vascularity has been demonstrated using conventional MRI (19,20).…”
Section: Discussionmentioning
confidence: 98%
“…Hulka et al (12) initially published a series of 22 lesions and found an overall positive, but not statistically significant, correlation between extraction-flow product and microvessel density. They further expanded their study to include 71 lesions and found an overall significant correlation between extraction-flow product and microvessel density, but the correlation was not significant in the subgroup of benign or malignant cancers (13). Studying 25 malignant and 23 benign lesions, Stomper et al (15) found a significant association between increased intratumor vessel density (factor VIII) and greater MR enhancement, but not with the washout rate.…”
Section: Discussionmentioning
confidence: 99%
“…We only included malignant cancers in this series. Benign lesions often had lower early enhancements and lower vascular density (12,13). If benign lesions were to be included, the spectrum would be widened and an improved correlation should be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Some studies have shown the rapid uptake patterns of invasive cancers on DEC-MRI reflect high intratumor angiogenesis. 12,13 It has been reported that DCE-MRI is useful for the differential diagnosis of some tumors, and many investigators have attempted to identify the differences between benign and malignant tumors by analyzing curve patterns such as rapid uptake or gradual increase from the time course of dynamic contrast enhancement. 14, 15 Therefore, we may be able to differentiate unilocular cystic lesions including ameloblastomas by detecting nodular regions on CE-MRI and/or DEC-MRI, or by detecting areas of high intratumor angiogenesis on DEC-MRI.…”
Section: Introductionmentioning
confidence: 99%